Effect of TH2 cytokines and interferon gamma on beat frequency of human respiratory cilia - Große-Onnebrink, Jörg; Hörmann, Karl (Pediatric research, 2016)
Background:In asthmatic airways secondary ciliary dyskinesia contributes to impaired mucociliary clearance. To investigate underlying mechanisms, we studied the effects of cytokines associated with asthma phenotype on the ciliary beat frequency (CBF) in a cell culture model of ciliated human respiratory epithelial cells.Methods:Nasal respiratory epithelial cells of 21 patients were used to prepare multicellular cells (spheroids) in the presence of the T helper (TH) 2 cytokines interleukin (IL)-4, IL-5, IL-9 and IL-13, and the TH1 cytokine interferon gamma (IFN-γ). CBF was determined by high-speed video microscopy.Results:Addition of IL-4 and IL-13 and IL-4 + IL-13 decreased the mean CBF by 17, 21, and 22%, respectively, compared with untreated controls. Addition of IL-5 and IL-9 lead to an increase in mean CBF (20 and 10%, respectively). Lower concentrations of IFN-γ (0.1 and 1 ng/ml) decreased mean CBF and higher concentrations (10 ng/ml) increased CBF by 6%. Addition of IFN-γ to IL-13 reversed the effect of IL-13 on the CBF of spheroids.Conclusion:Cytokines directly influence the ciliary function of respiratory epithelium and contribute to the impaired mucociliary clearance in asthmatic disease. Our study encourages further research to investigate IFN-γ as a treatment option in diseases with impaired mucociliary clearance like asthma.
Gesehen am 06.05.2019